Pregnancy-associated breast cancer: a case report and literature review - Van Der Hock, Sarah; Chintamani, Alekhya; Bulloch, Gabriella; Seth, Ishith; Dhupar, Nita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Pregnancy-associated breast cancer (PABC) is a rare, yet significant clinical entity which presents itself during pregnancy or within one year postpartum. This case report and literature review discusses the case of a 33-year-old G1P0 woman diagnosed with PABC at 38 weeks’ gestation with an uncomplicated pregnancy and no significant risk factors. Fine needle aspiration revealed a left-sided metaplastic grade 3 invasive ductal carcinoma with heterogeneous mesenchymal differentiation and focal ductal carcinoma in situ, and an uncomplicated nipple-sparing mastectomy was undertaken at three weeks’ post-partum. This case report emphasises the need for early diagnosis and the importance of screening for breast cancer during pregnancy, and advocates for a low threshold to screen for PABC in all pregnancies. The literature review also provides updated insights into the presentation, diagnosis, and management of PABC. We explore the diagnostic challenges associated with PABC, including physiological changes in breast tissue during pregnancy, limitations of imaging modalities, and the importance of considering PABC as a differential diagnosis.